ESSENSI GANTI RUGI IMMATERIEL DALAM PERBUATAN MELANGGAR HUKUM MENURUT PUTUSAN HAKIM PERDATA INONESIA - Markus Suryoutomo (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2019)
Legal findings by judges in interpreting the meaning of the text of the Act can function to realize and provide protection for the community of justice seekers, National legislation and its conclusions in the form of court decisions are reported to be open to various studies and deconstructive criticism that carried out through various social movements that care about the law, so that national law can function as one of the forces to mobilize the lives of new Indonesian people who are able to act responsively for the public interest. From this definition the obligation of the Judge to uphold justice comes from its authority, namely the Judicial Discretion policy. In the event that the judge grants Maternity compensation to the Law Breaking Lawsuits, insofar as it has fulfilled the Elements of Article 1365 of the Civil Code, which brings the legal consequences the judge can grant Immaterial compensation based on found